Suggested Weed Control Programs for Citrus - Stephen H. Futch; Brent Sellers (EDIS, 2016)
Weed management is an important component of citrus production. The selection and implementation of a weed management program can lead to both economic and environmental returns. This revised 3-page fact sheet details how to manage weeds in both young and mature groves, the differences in weed control programs between interior areas and coastal or flatwoods areas, how to control weeds after a freeze, and common ways that herbicides are misused. Written by Stephen H. Futch and Brent Sellers, and published by the Horticultural Sciences Department, September 2015.